2017
DOI: 10.5005/jp-journals-10024-2046
|View full text |Cite
|
Sign up to set email alerts
|

Apical Periodontitis and Endodontic Treatment in Patients with Type II Diabetes Mellitus: Comparative Cross-sectional Survey

Abstract: Aims:The aims of this study were to investigate the prevalence of apical periodontitis (AP) in diabetes mellitus (DM) patients compared with nondiabetic patients and to examine the effect of glycemic control on the prevalence of AP. Materials and methods:Radiographs of a group of DM patients were compared with those of a matched nondiabetic group to identify AP. The diabetic group was subdivided according to the level of glycemic control into two subgroups: A well-controlled DM and a poorly controlled DM. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(75 citation statements)
references
References 39 publications
4
67
1
3
Order By: Relevance
“…According to the authors, diabetes may serve as a disease modifier of AP in the sense that individuals with diabetes can be more prone to develop primary disease. In agreement with the previous studies, Smadi 35 found that there is a higher prevalence of AP in diabetes mellitus patients compared with that in the nondiabetic group, with an increased prevalence of persistent chronic AP. In comparison with well-controlled diabetes, poor glycemic control may be associated with a higher prevalence of AP and an increased rate of endodontic failures.…”
Section: Continuationsupporting
confidence: 91%
“…According to the authors, diabetes may serve as a disease modifier of AP in the sense that individuals with diabetes can be more prone to develop primary disease. In agreement with the previous studies, Smadi 35 found that there is a higher prevalence of AP in diabetes mellitus patients compared with that in the nondiabetic group, with an increased prevalence of persistent chronic AP. In comparison with well-controlled diabetes, poor glycemic control may be associated with a higher prevalence of AP and an increased rate of endodontic failures.…”
Section: Continuationsupporting
confidence: 91%
“…, Arya et al . , Smadi ), and four others did not present results on the frequency of tooth extraction after NSRCT in diabetics and controls (Fouad & Burleson , Doyle et al . , Lin et al .…”
Section: Reviewmentioning
confidence: 94%
“…Levels of evidence in humans. An association between apical periodontitis and diabetes was found in seven of these experimental studies with an n value of 455 positive cases (76.47%) [11,33,35,40,41]. However, in one study [34] with an n value of 62 individuals (4.28%), they reported no statistical significance between these two entities and on two studies, they did not report whether or not an association was established, main outcomes are reflected on Table 1 and Table 2.…”
Section: Quality Assessmentmentioning
confidence: 94%
“…Only four articles met the inclusion criteria: 2 studies in animals [38,39] and 2 studies in humans [40,41]. Finally, 21 article were included, 10 studies in animals [22][23][24][25][26][27][28][29]38,39], 10 studies in humans [30][31][32][33][34][35][36][37]40,41] and 1 systematic review [11] (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%